Method of increasing the longitudnal current of Н⁻ ions from pig with a metal-hydride cathode - Sereda, I.N.; Tseluyko, A.F.; Ryabchikov, D.L.; Hrechko, Ya.O.; Krupka, A.A. (Вопросы атомной науки и техники, 2019)
The possibility of increasing the current of negative hydrogen ions extracted in the longitudinal direction from Penning discharge with a metal-hydride cathode by changing potentials at the discharge cathodes is investigated. An electromagnetic filter is used to separate negative ions from the extracted flux of charged particles. A significant correlation between the extracted total current and the current of negative ions from the cathode potential was found. The optimal parameters for the effective extraction of H⁻ ions are determined. The current of the H⁻ ion beam at a level of 10 μA was obtained. Досліджується можливість збільшення струму негативних іонів водню, видобутих у поздовжньому напрямку з розряду Пенінга з металогідридним катодом шляхом зміни потенціалів на катодах розряду. Для сепарації негативних іонів, що витягаються з потоку заряджених частинок, застосовується електромагнітний фільтр. Виявлена суттєва кореляція загального струму і струму негативних іонів від потенціалу катодів. Визначено оптимальні параметри для ефективного вилучення іонів Н⁻ . Отримано струм пучка іонів Н⁻ на рівні 10 мкА. Исследуется возможность увеличения тока отрицательных ионов водорода, извлекаемых в продольном направлении из разряда Пеннинга с металлогидридным катодом, путем изменения потенциалов на катодах разряда. Для сепарации отрицательных ионов из извлекаемого потока заряженных частиц применяется электромагнитный фильтр. Обнаружена существенная корреляция извлекаемого общего тока и тока отрицательных ионов от потенциала катодов. Определены оптимальные параметры для эффективного извлечения ионов Н⁻. Получен ток пучка ионов Н⁻ на уровне 10 мкА.